2006
DOI: 10.1007/s11589-002-0155-2
|View full text |Cite
|
Sign up to set email alerts
|

Research on distinguishing method and mechanism of tidal deformation anomalies before large earthquakes

Abstract: By analyzing the digital tilt tidal observations at Yongsheng station and strain tidal observations at Houma station, this paper suggests that the solid tidal force might trigger tiny abrupt deformation when the seismogenic system enters into an instable critical state. The step and abrupt changes correlate to a certain extent to the direction of tidal force and the orientation and size of tidal shear stress along the fault strike. In the paper, we study for the first time the relationship between deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Carbon aerogels (CAs) are considered to be perfect electrode materials for electrochemical capacitors due to their unique three-dimensional nano-network, high specific surface area, abundant mesopores and high electric conductivity [2][3][4]. According to reports in the literature, it can be concluded that many factors affect the electrochemical performance of supercapacitors, including their specific surface area, pore volume, pore size distribution, as well as the surface groups of the electrode materials [4][5][6][7][8]. Meng et al reported that both the surface area and pore volume of carbon aerogels determine their specific capacitance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon aerogels (CAs) are considered to be perfect electrode materials for electrochemical capacitors due to their unique three-dimensional nano-network, high specific surface area, abundant mesopores and high electric conductivity [2][3][4]. According to reports in the literature, it can be concluded that many factors affect the electrochemical performance of supercapacitors, including their specific surface area, pore volume, pore size distribution, as well as the surface groups of the electrode materials [4][5][6][7][8]. Meng et al reported that both the surface area and pore volume of carbon aerogels determine their specific capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…Azais et al indicated that the concentration of surface groups and their nature were found to have an important influence on the performance degradation of supercapacitors [7]. Zhuang et al reported that activated carbons with larger micropores have a larger specific capacitance and a higher discharge rate [8]. Summarizing the reported results in the literature, it was found that the electrochemical capacitance is generally proportional to the specific surface area for the same kind of carbon materials, but this relation is not necessarily valid when comparing different kinds of carbon materials.…”
Section: Introductionmentioning
confidence: 99%